Public health nursing education viewed through the lens of superdiversity: a resource for global health - Cécile-Marie Dupin; Mélanie Pinon; Karine Jaggi; Celina Teixera; Aurèle Sagne; Noelia Delicado (BMC, 2020)
Abstract Background Nurses are increasingly confronted with the challenge of globalization and the acceleration of migratory flows. This reality affects the notion of culture and its influence on health-related behaviors. The state of health of the population in the Canton of Geneva, where there is a wide diversity of origins, is characterized by significant differences. The term "superdiversity" is used to describe the increasing complexity in ethnic diversity due to migration and social stratification. Nursing education in Geneva, influenced by the Bologna Process, appears appropriate for superdiverse contexts of care, with the development of dedicated competencies. Aim This discussion paper aims to examine the academic curricula implemented in Geneva in the light of the concept of superdiversity. Main text In Geneva, nursing education and curricula in public health are based on a competence framework for nursing care divided into 7 roles and educational tracks. Bachelor's-level nurses know how to assess a care problem quickly and solve it effectively by setting relevant priorities, and do so based on evidence. The curricula aim to teach nurses to design population and individual interventions in their superdiverse context. Discussion Education should enable students to develop their role as health promoters for the well-being of patients and communities, taking into account cultural complexity. Conclusions Superdiverse contexts highlight the role of nurse educators in preparing future generations of public health nurses.